Association of Nutritional Risk Index With Postoperative Pain Outcomes in Elderly Patients Undergoing Gastrointestinal Surgeries: A Retrospective Cohort Study - Zheng, Hua; Duan, Guangyou; Shen, Shiqian; Zhang, Xianwei (Frontiers in Medicine, 2021)
Background: Malnutrition is a major health problem, which is common in hospitalized elderly patients and is associated with an increased risk of morbidity and mortality. However, studies on malnutrition and its effect on postoperative pain outcomes in elderly patients have been largely neglected. Here we investigated the relationship between nutritional risk and postoperative pain outcomes in elderly patients. Methods: Between April 1, 2012, and August 31, 2015, 734 elderly patients (≥65 years) who underwent gastrointestinal surgeries were recruited and assigned into two groups according to geriatric nutritional risk index (GNRI). All patients received standard anesthesia procedures and postoperative patient-controlled analgesia for 48 h. The preoperative epidemiology data and postoperative outcome data including pain intensities at rest and movement, the cumulative consumption of analgesics and its common side effects were recorded. Results: The total number of patients with high nutritional risk (GNRI < 92) was 533 out of 734 (72.62%). When compared with low nutritional risk individuals (GNRI ≥ 92), the incidence of inadequate analgesia was significantly higher in elderly patients with GNRI < 92 at different time points. In addition, the cumulative consumption of analgesics was also significantly higher in elderly patients with GNRI < 92 at 0–6 h postoperatively. Through logistic regression analysis, high nutritional risk (OR = 3.113, 95% CI: 1.661–5.834, P < 0.001) and female gender (OR = 0.606, 95% CI: 0.394–0.932, P = 0.023) were identified as significant predictors for postoperative inadequate analgesia. Further sensitivity analyses showed high nutritional risk as a predictor for postoperative inadequate analgesia was more prominent in female patients and early elderly patients. Moreover, 88 was determined as an optimal cut-off value of GNRI for postoperative inadequate analgesia using receiver operating characteristic curve analysis. Conclusion: High nutritional risk is associated with poor postoperative pain outcomes in gastrointestinal elderly patients. Preoperative nutritional evaluation using simple nutritional screening instruments (e.g., GNRI) with the new suggested cut-off value (GNRI = 88) might be included as a standard procedure in routine clinical practice among these patients for postoperative analgesia.